2020
DOI: 10.29210/147800
|View full text |Cite
|
Sign up to set email alerts
|

Teacher strategies in online learning to increase students’ interest in learning during COVID-19 pandemic

Abstract: Interest has a very important role in learning. This interest leads to motivation in learning and it can improve learning outcomes. This study focused on understanding and exploring the strategies used by teachers of SDIT Rabbi Radhiyya Curup to increase student's interest in learning and to express students' responses in Online learning during the COVID-19 pandemic. This research is qualitative research with a phenomenological approach in which the principal, the vice-principal of curriculum, the teachers, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0
20

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(151 citation statements)
references
References 28 publications
(29 reference statements)
7
124
0
20
Order By: Relevance
“…Selain media video dosen juga harus menyediakan sumber belajar lain seperti modul, buku elektronik, dan bahan ajar ringkas lainnya. Bahan ajar yang disajikan dalam pembelajaran online diusahakan dikembangkan sendiri oleh dosen dengan mempertimbangkan berbagai aspek seperti bahan ajar harus ringkas, menarik dan memotivasi mahasiswa (Sutarto, Sari & Fathurrochman, 2020).…”
Section: Gambar 5 Grafik Respon Mahasiswa Terhadap Jenis Bahan Pembelajaran Yangunclassified
“…Selain media video dosen juga harus menyediakan sumber belajar lain seperti modul, buku elektronik, dan bahan ajar ringkas lainnya. Bahan ajar yang disajikan dalam pembelajaran online diusahakan dikembangkan sendiri oleh dosen dengan mempertimbangkan berbagai aspek seperti bahan ajar harus ringkas, menarik dan memotivasi mahasiswa (Sutarto, Sari & Fathurrochman, 2020).…”
Section: Gambar 5 Grafik Respon Mahasiswa Terhadap Jenis Bahan Pembelajaran Yangunclassified
“…Students are required to change their learning method from in-class to online learning. As stated by Sutarto et al (2020) the learning process, initially was conducted face-to-face in the classroom, but has been shifted to home learning using the online system or distance learning (Nasir et al, 2018) through the use of various existing media. The online learning was used for their daily lesson and to assess their academic performance and it somehow causes the students to get stressed.…”
Section: Psychological Impact On Students During Covid-19mentioning
confidence: 99%
“…A large body of research have shown that parent-teacher collaboration contributes to overall school effectiveness [39,47,82]. Parent and teacher collaboration is vital for the academic and personal growth of students [64].…”
Section: Strategies For Onsite Learning Post Sars-cov-2mentioning
confidence: 99%
“…Teachers can make a simple phone call to their students' parents or text them to help continue education at home. Sutarto and Sari [82] added that parent and teachers are considered as partners who can work together to ensure the success of learning. Inadequate cooperation between parent and teachers can affect student academic outcomes.…”
Section: Strategies For Onsite Learning Post Sars-cov-2mentioning
confidence: 99%